Four essays on writing economic history of colonial India - Bagchi, Amiya Kumar; Acharya, Jayanta; Ghosh, Subhasri; Mukherjee, Jenia; Institute of Development Studies, Kolkata (Kolkata : Published by Institute of Development Studies in association with Progressive Publishers, 2011)
Papers presented at a workshop on Writing and teaching of economic history, held at Kolkata on 8th December 2010.
Includes bibliographical references.
Keywords: ECONOMIC HISTORY -- 19th century -- Congresses; COLONIAL INDIA; ESSAYS; INDIA -- Economic conditions -- 19th century -- Congresses